1991
DOI: 10.1007/bf02470913
|View full text |Cite
|
Sign up to set email alerts
|

Dumbbell neurogenic tumor of the mediastinum: A report of three cases undergoing single-staged complete romoval without thoracotomy

Abstract: Of a total thirteen patients who underwent surgery for a neurogenic tumor in the posterior mediastinum 4 (30.8 per cent) presented with dumbbell type development of the tumor. Along with a comparatively greater incidence in the number of cases of dumbbell neurogenic tumors in the posterior mediastinum, resection has also recently become more popular, necessitating the establishment of a standard operative approach for this type of tumor. We successfully removed dumbbell neurogenic tumor from the posterior medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…Ricci et al [19] reported using Akwari's and Grillo's approaches selectively, reserving the latter for smaller tumours. Other groups [20][21][22][23] preferred a laminectomy and a costotransversectomy without entering the pleural cavity or a combined laminectomy and thoracotomy in either one or two stages. Vallières et al [24] described 4 patients treated with a surgical approach involving posterior microneurosurgery combined with anterior VATS.…”
Section: Discussionmentioning
confidence: 99%
“…Ricci et al [19] reported using Akwari's and Grillo's approaches selectively, reserving the latter for smaller tumours. Other groups [20][21][22][23] preferred a laminectomy and a costotransversectomy without entering the pleural cavity or a combined laminectomy and thoracotomy in either one or two stages. Vallières et al [24] described 4 patients treated with a surgical approach involving posterior microneurosurgery combined with anterior VATS.…”
Section: Discussionmentioning
confidence: 99%
“…Due to recent case reports of paraplegia caused by swelled sponges in the postoperative period we advise to avoid application of similar materials or to use them with appropriate caution [16,17]. An interesting alternative to our technique is a dorsal approach, proposed by Osada et al [2], involving laminectomy and resection of a small portion of the adjacent rib without opening the parietal pleura. The avoidance of thoracotomy helps in postoperative pain control.…”
Section: Discussionmentioning
confidence: 97%
“…In the majority of cases they are neurogenic benign tumors which have their origin in the neuron sheath (68%), parasympathic ganglion (30%) or paraganglionic cells (2%) [2]. Only 3 -19% of such tumors, usually in children, are malignant.…”
Section: Introductionmentioning
confidence: 99%
“…[19] In a large number of cases, by Ozawa et al , the dumbbell tumors were excised through a hemilaminectomy and a facetectomy with the spinal stabilization/reconstruction by Rogers wiring and contralateral facet fusion, leaving the spinous process, supra- and intraspinous ligaments, and contralateral facet joint intact. [20] However, we are of the opinion that in large intradural/intraspinal tumors with cord compression and displacement, full laminectomy is safer over hemilaminectomy and protects the cord from trauma.…”
Section: Discussionmentioning
confidence: 99%